12-month results of the standardised combination therapy for diabetic macular oedema: intravitreal bevacizumab and navigated retinal photocoagulation. Issue 8 (10th April 2014) - Barteselli, Giulio; Kozak, Igor; El-Emam, Sharif; Chhablani, Jay; Cortes, Marco A; Freeman, William R
Abstract : Aim: To evaluate the efficacy of a standardised combination therapy for clinically significant diabetic macular oedema using bevacizumab injections followed by navigated laser photocoagulation to stabilise retinal thickness. Methods: In this pilot study we retrospectively reviewed charts and imaging of 23 eyes treated with the standardised combination regimen. Eyes initially received monthly bevacizumab injections, followed by navigated laser photocoagulation when central retinal thickness (CRT) was <440 µm. Patients were then followed monthly for 12 months. Results: At the time of navigated laser after bevacizumab treatment mean vision gain was +10.4 Early Treatment Diabetic Retinopathy Study letters (p<0.01) and CRT reduction was 146 µm (p<0.001). At 12 months from baseline, the vision gain remained stable at +10.6 Early Treatment Diabetic Retinopathy Study letters (p<0.01), and CRT reduction was stable at 137 µm (p<0.001). At 12 months from laser, the vision gain was 7.8 letters from baseline (p<0.01), with no significant change compared with the gain at 12 months from baseline (p=0.108). At 12 months from laser, CRT reduction was 125 µm from baseline (p<0.001), with no significant change compared with CRT reduction at 12 months from baseline (p=0.601). Total injections needed were 4.4 from baseline to month 12, with 1.3 reinjection needed after laser. 57% of the eyes didn't require injections after laser, while 43% needed two additional injections. Conclusions: Standardised combination therapy using bevacizumab injections followed by navigated laser treatment for clinically significant diabetic macular oedema demonstrated significant visual gain and CRT reduction after bevacizumab treatment and stabilisation after navigated laser up to 12 months. The number of injections required in 12 months was lower than reported in previous combination studies.